Formation of streams of binary sequences with controlled structure of "cellular" automata in homogeneous register environments - P. A. Kadiev; K. K. Nazarov; Z. G. Kardashova (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. Development of a method for organizing the process of forming flows register structure, patented by the author at the Department of DSTU, which is a cellular automaton of binary sequences with a controlled structure of "cellular" automata in homogeneous register environments. Method. To solve the set system problem, a process model was built in order to determine the factors that allow changing the sequence of flow elements. Result. When studying the most common generators of pseudo-random streams based on linear register media with modulo two adders in feedback circuits, which are "cellular" automata, it was established from the tables of environment states that the factors determining the structure of the generated streams of binary sequences are the sequence of states , are the initial state of the register of a homogeneous medium and the feedback structure determined by the transition function of the cellular automaton. Conclusion. It is shown that by varying the initial state of the cellular automaton and the structure of feedbacks as control tools, it seems possible to form binary pseudo-random streams of states with different structures, different order of flow elements, bringing their characteristics closer to random ones. Examples of the implementation of the flow structure control process are given, confirming this assumption. A typical structure of a stream shaper with a managed structure based on a homogeneous one is given.